Instrumen Open Ended Sebagai Alat Diagnostik Hambatan Epistemologi pada Materi Bilangan Berpangkat: Systematic Literature Review - Fitrianiayuningsih, Niputu Bela; Suharta, I Gusti Putu; Ardana , I Made (Media Pendidikan Matematika, 2026)
This study aims to synthesize current literature on the effectiveness of open ended instruments in detecting students’ epistemological obstacles, particularly in the topic of exponents. A Systematic Literature Review (SLR) using the PRISMA protocol was conducted on 15 relevant scientific articles published between 2020 and 2026 from the Google Scholar, ERIC, and Scopus databases. The synthesis reveals that epistemological obstacles in exponent material are hierarchical and cumulative in nature, with conceptual obstacles at the root that systematically give rise to procedural and operational obstacles. Open-ended instruments prove highly effective both as diagnostic tools and as stimulants for Higher Order Thinking Skills (HOTS), as their divergent characteristics transparently externalize students’ thinking processes. This study produces a triple-function model of open-ended instruments (diagnostic, stimulative, and formative) along with a conceptual framework linking open-ended instruments, epistemological obstacles, HOTS, and mathematical literacy. It is recommended that educational practitioners integrate open-ended instruments into periodic diagnostic assessments to mitigate learning obstacles at an early stage.